2018
DOI: 10.3390/f10010020
|View full text |Cite
|
Sign up to set email alerts
|

Generating Tree-Level Harvest Predictions from Forest Inventories with Random Forests

Abstract: Wood supply predictions from forest inventories involve two steps. First, it is predicted whether harvests occur on a plot in a given time period. Second, for plots on which harvests are predicted to occur, the harvested volume is predicted. This research addresses this second step. For forests with more than one species and/or forests with trees of varying dimensions, overall harvested volume predictions are not satisfactory and more detailed predictions are required. The study focuses on southwest Germany wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 47 publications
4
19
0
Order By: Relevance
“…The introduction of new technologies should allow for the rapid recovery of a forest [20] that can bind carbon from the atmosphere [19,20], produce wood that can serve as a biofuel [21], and retain more water in the landscape, thereby cooling the atmosphere. The secondary impact of rapid forest recovery is the long-term stabilization of annual logging [22][23][24] and hence also the stabilization of wood prices [25][26][27][28], including the sustainability of the whole foresty sector [29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of new technologies should allow for the rapid recovery of a forest [20] that can bind carbon from the atmosphere [19,20], produce wood that can serve as a biofuel [21], and retain more water in the landscape, thereby cooling the atmosphere. The secondary impact of rapid forest recovery is the long-term stabilization of annual logging [22][23][24] and hence also the stabilization of wood prices [25][26][27][28], including the sustainability of the whole foresty sector [29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The RF is a decision tree algorithm and an effective machine learning model for predicting a forest of variables. Based on its powerful modeling capabilities, the RF regression has been widely used in scientific research [94][95][96][97][98][99]. The principle of the RF algorithm is to use the bootstrap method to randomly extract multiple samples to generate a group of regression trees (ntree) from the original sample population.…”
Section: Statistical Models For Estimating the Fsvmentioning
confidence: 99%
“…While this accuracy differential between multilevel models has been demonstrated universally in regression contexts, it is presently shown to remain relevant in classification contexts. Furthermore, while results by Speiser et al (2019, 2020) and Kilham et al (2019) have demonstrated that conditions may exist in which single-level classification trees and random forests may outperform their multilevel analogues, this study adds to the debate of the necessity of multilevel classifiers through a demonstration of NB’s efficacy under multilevel data conditions. These results bolster the findings of Demichelis et al (2006) and Zhang et al (2018) illustrating that NB does perform comparably to or greater than the multilevel Bayes classifier (among others) under the same conditions.…”
Section: Discussionmentioning
confidence: 75%
“…The GMERT models consistently outperformed the GLMML variants on measures of predictive mean absolute deviation and predictive misclassification rates; to date, this represents the most comprehensive simulation study on multilevel classifiers. Expanding on this finding, Kilham et al (2019) compared REEMTree, MERF, and GLMML, with MERF performing best on measures of both variance explained and root mean squared error in harvest prediction data. Capitaine et al (2019) also found substantially reduced bias in estimates for MERF above REEMTree and GLMML in the context of both simulated and archival low- and high-dimensional genetic data.…”
Section: Previous Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation